Beyond the Academy: Applying Anthropological Research, A Case Study of Demonstrating Impact in the U.K. 2014 REF. (1st June 2015) - Jarman, Neil; Bryan, Dominic
Abstract : The 2014 Research Excellence Framework sought for the first time to assess the impact that research was having beyond the boundaries of the university and the wider academic sphere. While the REF continued the approach of previous research assessment exercises in attempting to measure the overall quality of research and teaching within the higher-education sector, it also expected institutions to evidence how some of their research had had 'an effect on, change or benefit to the economy, society, culture, public policy or services, health, the environment or quality of life, beyond academia' (REF 2012: 48). This article provides a case study in how researchers in one U.K. anthropology department were able to demonstrate the impact of their work in the public sphere successfully as part of this major audit exercise.